Initial placement and secondary displacement of a new suture‐method catheter for sciatic nerve block in healthy volunteers: a randomised, double‐blind pilot study1. (25th May 2017) - Lyngeraa, T. S.; Rothe, C.; Steen‐Hansen, C.; Madsen, M. H.; Christiansen, C. B.; Andreasen, A. M.; Lundstrøm, L. H.; Lange, K. H. W.
Summary: We performed a randomised double‐blind pilot study in 16 healthy volunteers to investigate the success rate for placing a new suture‐method catheter for sciatic nerve block. A catheter was inserted into both legs of volunteers and each was randomly allocated to receive 15 ml lidocaine 2% through the catheter in one leg and 15 ml saline in the other leg. Successful placement of the catheter was defined as a 20% decrease in maximum voluntary isometric contraction for dorsiflexion of the ankle. Secondary outcomes were maximum voluntary isometric contraction for plantar flexion at the ankle, surface electromyography and cold sensation. After return of motor and sensory function, volunteers performed standardised physical exercises; injection of the same study medication was repeated in the same leg and followed by motor and sensory assessments. Fifteen of 16 (94%; 95%CI 72–99%) initial catheter placements were successful. The reduction in maximum voluntary isometric contraction and surface electromyography affected the peroneal nerve more often than the tibial nerve. Eleven of 15 (73%; 95%CI 54–96%) catheters remained functional with motor and sensory block after physical exercise, and the maximal displacement was 5 mm. Catheters with secondary block failure were displaced between 6 and 10 mm. One catheter was displaced 1.8 mm that resulted in a decrease in maximum voluntary isometric contraction of less than 20%. After repeat test injection, 14 of the 16 volunteers had loss of cold sensation. Neither motor nor sensory functions were affected in the legs injected with placebo. We conclude that the suture‐method catheter can be placed with a high success rate, but that physical exercise may cause displacement.